2015
DOI: 10.1039/c5cc05728k
|View full text |Cite
|
Sign up to set email alerts
|

Switching of inherent chirality driven by self-assembly

Abstract: Dynamic chirality of iminoresorcin[4]arenes that originates from regioselective and diastereoselective keto-enol tautomerisation was switched by non-covalent interactions with achiral molecules, as demonstrated by experimental electronic circular dichroism (ECD) spectra supported by TD DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…28 Both types of products are stabilized by directional seams of intramolecular hydrogen bonds, which, in addition to stabilization, results in inherent chirality of the molecules. 29 Currently, we used a bifunctional semi-rigid building block -hydrazineexpecting formation of covalently connected cages ( Fig. 1).…”
mentioning
confidence: 99%
“…28 Both types of products are stabilized by directional seams of intramolecular hydrogen bonds, which, in addition to stabilization, results in inherent chirality of the molecules. 29 Currently, we used a bifunctional semi-rigid building block -hydrazineexpecting formation of covalently connected cages ( Fig. 1).…”
mentioning
confidence: 99%
“…These bands are the most sensitive to conformational inherent chirality and symmetry of these molecules, as they come from the HOMO-LUMO transition involving an inherently chiral chromophore. 25 These results indicate that the capsular dimers indeed retain a hydrogenbonded ordered structure in competitive medium. It is also important to note that there are no traces of dynamic exchange between species at the NMR timescale, indicating that the complexes are also kinetically persistent in this solvent, which is quite surprising considering that semi-open cavitands are also present in the solution.…”
mentioning
confidence: 80%
“…We have previously found that self-assembly has a pronounced effect on ECD spectra. [14,17,18] This is primarily due to the increased rigidity and conformational order of self-assembled structures compared to the conformationally labile cavitands.A fter self-assembly,r otations about partial double bonds becomeh indered, and inherently chiral conformations are generated, which result in as ignificant intensity increase (by even two orders of magnitude)o fE CD bands [18] or inversion of the sign of the Cotton effect. [17] In the current experiments,t he increase of band intensity indicates that, during the templated reactions, highly ordereds pecies must be formed that are fundamentally different from the cavitands obtained by nontemplated procedures.…”
Section: Structure and Stability In Watermentioning
confidence: 99%